2004
DOI: 10.1007/s00056-004-0229-y
|View full text |Cite
|
Sign up to set email alerts
|

Orofacial Development in Children with Down?s Syndrome 12 Years after Early Intervention with a Stimulating Plate

Abstract: According to the results of the present study, the orofacial status in early childhood is decisive for the subsequent development of the orofacial region and the long-term stability of the achieved improvements: Children with a pronounced orofacial dysfunction showed a greater stimulation-plate-induced improvement than those with initially moderate orofacial findings. This observation was confirmed by the findings of the 12-year follow-up: Children with Down's syndrome and initially slight orofacial impairment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
15

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 17 publications
(68 reference statements)
1
19
0
15
Order By: Relevance
“…The parents reported that increased muscle tension also continued after the plate had been removed; thus they observed a visible improvement in their child's facial features. This was also confirmed by Krombacher et al [25], who conducted long-term observations of patients with DS who had undergone early orofacial therapy through the use of a palatal plate.…”
Section: Internetsupporting
confidence: 64%
“…The parents reported that increased muscle tension also continued after the plate had been removed; thus they observed a visible improvement in their child's facial features. This was also confirmed by Krombacher et al [25], who conducted long-term observations of patients with DS who had undergone early orofacial therapy through the use of a palatal plate.…”
Section: Internetsupporting
confidence: 64%
“…Underdevelopment of the midface bones is common, causing a shortened palate in the anteroposterior dimension [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…2,14,19,20 Muscle hypotonia associated with a reduced volume of the oral cavity and characterized by a deep, atresic palate may lead to a tendency toward habitually projecting the tongue against the teeth or outside the mouth. 5,18,21 Abnormal function and the position of the tongue can affect tooth eruption causing anterior open bite, tooth alignment, and the arch shape. 12,22 However, these variables were not assessed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,3 Patients with this syndrome exhibit cognitive impairment as well as bone growth disorders and generalized muscle hypotonia. 4,5 Moreover, oral health problems, such as inadequate oral hygiene, periodontal disease, caries, malocclusion, and tooth loss, are more prevalent in this group of individuals than in the general population. 6,7,8,9 Malocclusion, in particular, exerts a considerable negative impact on the quality of life, causing problems related to the performance of daily activities, such as speech, swallowing, and chewing, and discrimination based on physical appearance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation